Alegorias do autoritarismo: a personagem mutilada em Yaka e Quarup - Vidal, Francisco Elder Freitas (2023)
Whether in Brazil under the military dictatorship in 1964 or in Angolaunder salazarist yoke, literature always imposed itself as a zone of crossings, intersections and discoveries of directions and misdirections able to reveal powerful nuances of existence and creation. That is how we came across Quarup and Yaka, works produced respectively by Antonio Callado and Pepetela, authors who were committed to aspects that went beyond documentary writing and linked to an understanding of literature as a space of full integration between form and content. By means of the aesthetic allegorical resource, they made possible not the historical record, but the perception of its ruins as an instrument of ungagging silenced voices. Committed to a view of allegory based on the thought of Walter Benjamin, both authors enabled the dialogue between present and past, resurrecting hitherto unprecedented visions of those times marked by pain and repression, violent times when the authoritarian state imposed itself by force, ripping, cutting and annihilating bodies, not caring about developing a pro-life policy, but rather one in the service of death, known as necropolitics. Amidst this rubble, we found the structural category that is the leitmotiv of our thesis, that of the mutilated character. Through it, we will show that mutilation in literature is something that goes beyond the physical aspect, spreading to other areas of violence such as those of a moral and psychological nature. Starting from mutilated character analysis, with these three approaches we will build all our study, showing how diverse, dynamic and intense the field of denunciation literature is. For each subcategory of mutilation we will reveal facets (some unprecedented) of the vast arsenal of violence that stained the pages of both Brazilian and Angolan literature. As bibliographic support we will base our research on authors such as Agamben (2004), Arendt (2013), Bakhtin (1998), Benjamin (2011), Bobbio (1998), Candido (2009), Chaves (2005), Carvalhal (2006), Compagnon (2010), Coutinho (1994), Dalcastagné (1996), Fanon (1979), Foucault (2014), Forster (1969), Freud (2018), Gagnebin (2013), Ginzburg (2001), Hansen (2006), Laranjeira (1995), Lúcia Helena (1985), Horkheimer (1980), Kant (2018), Kothe (1976), Leite (1982), Lúkacs (2011), Macêdo (2009), Mbembe (2016), Memmi (2007), Massaud Moisés (1999),Moore (2007), Nitrini (2010), Rosenfeld (2009), Secco (2008), Seligmann-Silva (2003), Wood (2012), among others.